2014
DOI: 10.4236/ojn.2014.411080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asthma Educational Intervention on Self-Care Management of Bronchial Asthma among Adult Asthmatics

Abstract: Asthma is one of the most common chronic diseases worldwide [1]. Despite advancement in science and technology and pharmacological revolutions, worldwide asthma prevalence is uncontrolled, morbidity and mortality from asthma. The most common reasons are non adherence to treatment, poor knowledge and skills in disease management [2]. Aim: The study aims to assess the impact of Asthma Education on self care management among Bronchial asthma patients. Objectives: 1) to assess the knowledge on self care management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Many studies worldwide have evaluated the effect of patient education and indicated that each of the above components is amenable to asthma education (6,7) . Thus, the task of patient education has become a key component of asthma management for asthma patients at all age groups (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies worldwide have evaluated the effect of patient education and indicated that each of the above components is amenable to asthma education (6,7) . Thus, the task of patient education has become a key component of asthma management for asthma patients at all age groups (8) .…”
Section: Introductionmentioning
confidence: 99%
“…If a patient understand the risks of non-compliance and benefits of compliance and believes the treatment is safe, it will improve their motivation and confidence to enhance their self-management practices. Hence providing right information on self-monitoring and adherence to medications, appropriate dietary measures and breathing exercises improves the disease control and reduces suffering due to frequency of acute attacks (Manchana and Mahal, 2014). Nurses could have a great contribution to promoting self-care capability in patients thanks to playing roles in training, coaching and guidance (Hemati et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The findings are also supported by the findings of the study of a quasi-experimental pre-test post-test research design conducted by Manchana V, Mahal R. in 2014 to assess the impact of asthma educational intervention on self-care management of bronchial asthma among adult. In this study out of 30 samples 1 (3.33%) had above average knowledge, 13 (43.33%) had average knowledge and 16 (53.33%) had below average knowledge, respectively in the pre-test knowledge score level [42] .…”
Section: Resultsmentioning
confidence: 56%
“…The present study findings are consistent with the findings of quasi experimental pretest post-test research design conducted by Manchana V, Mahal R in 2014 to assess the impact of educational intervention on self-care management of bronchial asthma among adult. The findings revealed that there was significant difference in knowledge before and after the planned educational intervention with mean difference 83,mean=2.8±1.22, df=29 and calculated t" value 12.72 at p value <0.05. respectively [42] . effective in gaining skill score regarding management of bronchial asthma [44] .…”
Section: Resultsmentioning
confidence: 99%